2016
DOI: 10.1016/j.jcrs.2015.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Scheimpflug lens densitometry and ocular wavefront aberrations in patients with mild nuclear cataract

Abstract: PURPOSE:To test correlations between Scheimpflug optical densitometry and ocular higher-order aberrations (HOAs) in patients with mild nuclear cataract.SETTING: Cornea and Refractive Surgery Department, Hospital de Braga, Braga, Portugal. DESIGN:Retrospective single-center study. METHODS:In eyes with mild nuclear cataract, lens densitometry was evaluated by Scheimpflug imaging (Pentacam HR), which provided an objective quantification (mean density and maximum density) and grading (nuclear staging score) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…These results are in agreement with Sachdev et al [ 21 ] and Rocha et al [ 22 ] who evaluated the level of high order aberrations (HOAs) in eyes with cortical and nuclear cataracts. On the contrast, Lee et al [ 23 , 24 ], Wu et al [ 25 ], and Faria-Correia et al [ 26 ], conversely to previous authors, reported that negative internal SA was increased in nuclear cataract as well as Kuroda et al [ 27 ] and Zhu et al [ 28 ] who also suggested that the opposite happens in cortical cataracts, with an increase of the positive total SA measured with Hartman–Sack aberrometers. This was attributed to the fact that wavefront in the central pupillary area relatively delays in nuclear cataracts and relatively advances in normal subjects and cortical cataract [ 27 ].…”
Section: Aging Of the Crystalline Lensmentioning
confidence: 93%
“…These results are in agreement with Sachdev et al [ 21 ] and Rocha et al [ 22 ] who evaluated the level of high order aberrations (HOAs) in eyes with cortical and nuclear cataracts. On the contrast, Lee et al [ 23 , 24 ], Wu et al [ 25 ], and Faria-Correia et al [ 26 ], conversely to previous authors, reported that negative internal SA was increased in nuclear cataract as well as Kuroda et al [ 27 ] and Zhu et al [ 28 ] who also suggested that the opposite happens in cortical cataracts, with an increase of the positive total SA measured with Hartman–Sack aberrometers. This was attributed to the fact that wavefront in the central pupillary area relatively delays in nuclear cataracts and relatively advances in normal subjects and cortical cataract [ 27 ].…”
Section: Aging Of the Crystalline Lensmentioning
confidence: 93%
“…Based on these measurements, the Pentacam can be equipped with software that then assigns a grade of nuclear sclerosis on a scale of 1–5 (Pentacam Nuclear Staging or PNS). The PNS score has been shown to correlate well with Snellen acuity and LOCS III grade, validating the Pentacam's automated assessment of nuclear sclerosis [67]. Furthermore, the Pentacam's densitometric parameters have been positively correlated with higher-order aberrations (HOAs) obtained from wavefront analyses [67].…”
Section: Cataract Evaluationmentioning
confidence: 91%
“…The PNS score has been shown to correlate well with Snellen acuity and LOCS III grade, validating the Pentacam's automated assessment of nuclear sclerosis [67]. Furthermore, the Pentacam's densitometric parameters have been positively correlated with higher-order aberrations (HOAs) obtained from wavefront analyses [67]. A consideration of HOAs may enable clinicians to better appreciate why patients with relatively good Snellen acuity may complain of poor vision quality.…”
Section: Cataract Evaluationmentioning
confidence: 96%
See 1 more Smart Citation
“…internal aberrations were calculated by subtracting the corneal wavefront aberrations from those of the entire eye measured by the ray-tracing aberrometer using the built-in program [7].…”
Section: Preoperative Assessmentmentioning
confidence: 99%